Institutional isomorphism in accounting innovations : Experience in the public and corporate sectors - Tóth, Balázs; Lippai-Makra, Edit (Economy & finance, 2024)
Accounting regulations and systems are subject to constant change. The evolution of accounting practices can be described as the outcome of different key factors. In this study, the authors examine two distinct areas of accounting, that of public sector accounting and of the corporate sector accounting using a neo institutional approach. The objective of the study is to present that, despite the differences of accounting in the two sectors, they can be examined within the same theoretical framework, and that different types of accounting innovation can be explained with institutional isomorphism. The research based on the relevant international and Hungarian literature indicates that certain groups of isomorphism can be observed in the diffusion of accounting practices. The normative one has proved to be the weakest and the coercive the strongest. It can also be concluded that in both public and corporate sector accounting innovations, the normative isomorphism emerges first, followed by the mimetic and finally the coercive one. As far as the authors are aware, this paper is the first of its kind in Hungary inasmuch as it reviews the two accounting subsystems within a uniform theoretical framework.